Applicability of simple power analysis to stream ciphers constructed using multiple LFSRs - Zadeh, A. A.; Heys, H. M. (2012 25th IEEE Canadian Conference on Electrical and Computer Engineering (CCECE), 2012)
In recent years, the hardware implementation of stream ciphers has attracted the interest of many designers, mainly due to their low implementation area on a chip. However, to date, in comparison with block ciphers, side channel attacks have not been extensively analyzed for their applicability to stream cipher hardware implementations. However it has been shown that simple power analysis (SPA) attacks are applicable to stream ciphers based on one linear feedback shift register. In this paper, we extend the SPA method to stream ciphers with multiple linear feedback shift registers and multiple linear feedback shift registers with irregular clocking. Then we apply the proposed method to the well-known stream ciphers E0 and LILI-128.